Analisis Semiotika Charles Sanders Peirce terhadap Pesan Dakwah dalam Film Assalamu'laikum Beijing 2: Lost In Ningxia - Diah Nuriyatul Jannah; Selvia Assoburu; Muslimin (ALAMTARA, 2026)
This study aims to analyze the Islamic preaching messages contained in the film "Assalamu'alaikum Beijing 2: Lost in Ningxia" through Charles Sanders Peirce's semiotic approach. This study employs a qualitative descriptive method with Peirce's triadic model of semiotic analysis, involving three main elements: representamen (sign), object, and interpretant. This approach was chosen because it can reveal layers of meaning hidden behind symbols, gestures, and dialogues in each scene. The focus of the analysis refers to the representation of preaching messages covering three categories: faith (aqidah), morals (akhlak), and sharia. The results show that this film consistently contains preaching messages across these three categories. The faith message is reflected in the understanding of the importance of always relying on and seeking help only from Allah; the moral message is seen through the values of guarding one's gaze, giving charity, and forgiving one another; and the sharia message is apparent in the obligation to cover the aurah, maintaining boundaries in interactions with the opposite sex, and teaching religious knowledge. This study contributes to the development of contemporary preaching studies based on audio-visual media and enriches the treasure of semiotic analysis in Islamic communication studies.